Kandungan Protein Kasar dan Serat Kasar pada Daun Kacang Tanah (Arachis hypogaea) yang Difermentasi dengan Bakteri Enterobacter cloacae WPL 111 sebagai Bahan Pakan Alternatif Ikan [ Content of Crude Protein and Crude Fiber in Peanut Leaves (Arachis hypogaea) Fermented by Enterobacter cloacae WPL 111 as Alternative Fish Feed Stuff] - Agustono Agustono; Widya Paramita Lokapirnasari; Karlina Hardianing Pangestu (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Feed is an element that really support the activities of aquaculture, there for the feed that is available must be adequate and meet the needs of the fish. Efforts to reduce feed costs, some farmers use alternative feed ingredients as a substitute for feed ingredients. Peanut leaves in the form of flour can be used as fish feed in pellet form. Peanut is potential biological resources to be used as feed to the waste produce sufficient forage nutritional value. Peanut leaves nutrition consist of, the dry matter 96,2754%, 29,7397% crude fiber, 17,2475% crude protein (Unit Inspection Services Consulting and Training of Faculty of Veterinary Medical Laboratory Airlangga University, 2014).This research been used Completely Randomized Design (CRD) method with five treatments and four replications. The treatment used were control (P0), the provision of Enterobacter cloacae WPL 111 5% (P1), 10% (P2), 15% (P3) and 20% (P4) with each repeated four times. Parameters observed were content of crude protein and crude fiber after fermentation for seven days in anaerob facultative. Data about the contain of crude protein and crude fiber obtained from this studied were analyzed with analysis of variants to determine the effect of treatment. Different between treatments were tested with Duncan;s multiple range test (DMRT). These results indicate that administration Enterobacter cloacae WPL 111 10% gave significant effect of the increase in crude protein content in the fermented leaves peanut and administration Enterobacter cloacae WPL 111 5% gave significant effect of the decrease in crude fiber content in the fermented leaves peanut. The suggested dosage to reduce the content of crude fiber and increase the crude protein content in the fermented leaves peanut is 10%.